EXPERIENCE OF BECOMING A WIDOW: A CASE STUDY AT LIMA PULUH KOTA DISTRICT - Putri, Mailana; Masril, Masril; Dasril, Dasril (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aims to explore the experiences of widowed women in Lima Puluh Kota District, focusing on social, psychological, and economic challenges they face. Method: A qualitative approach with a case study design was employed, utilizing primary data from widowed women and community leaders, along with secondary data from relevant documentation. Results: The findings reveal that widowed women in Lima Puluh Kota District experience profound emotional loss, social stigma, and changes in social roles, leading to feelings of isolation, anxiety, and insecurity. Economically, they face increased financial responsibilities, often relying on informal jobs or small businesses to meet their living needs. Despite these challenges, a process of recovery and self-empowerment is observed among some women. Novelty: This study provides a comprehensive understanding of the complex interplay between social stigma, psychological adaptation, and economic resilience among widowed women, contributing to the limited literature on widowhood experiences in rural Indonesian contexts.